2020
DOI: 10.1097/ans.0000000000000289
|View full text |Cite
|
Sign up to set email alerts
|

Framework for Patient and Informal Caregiver Participation in Research (PAICPAIR)

Abstract: The term user involvement is frequently applied in research. Frameworks for patient and informal caregiver participation as coresearchers in studies concerning patients with lifethreatening illness are however sparse. The PhD project Dying With Dignity-Dignity-Preserving Care for Older Women Living at Home With Incurable Cancer has implemented a thorough cooperation with patients and informal caregivers from the early stages of the research process. A framework for Patient and Informal Caregiver Participation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 41 publications
(33 reference statements)
0
27
0
Order By: Relevance
“…We suggest an increased focus on this issue in future research. In line with recommendations from the WHO, we suggest that research upon these matters include the involvement of persons with dementia and their informal caregivers [ 2 , 43 ].…”
Section: Discussionmentioning
confidence: 65%
“…We suggest an increased focus on this issue in future research. In line with recommendations from the WHO, we suggest that research upon these matters include the involvement of persons with dementia and their informal caregivers [ 2 , 43 ].…”
Section: Discussionmentioning
confidence: 65%
“…We included PAICPAIR as part of our methodological approach (Staats et al, 2019) and found this to be vital in strengthening the internal validity of the study. As members of the study reference group, the woman living with incurable cancer at home and the former informal caregiver strongly contributed in all phases of the research process (apart from the data collection).…”
Section: Methodological Considerations and Study Limitationsmentioning
confidence: 99%
“…User involvement improves the relevance and utility of research and gives insight into the user's unique experiences of everyday life (Morrow, 2012). A framework for Patient and Informal Caregiver Participation in Research (PAICPAIR) suggests a stronger foundation for democracy, equality and research quality by promoting active participation among vulnerable people experiencing incurable, life-threatening illness, as co-researchers (Staats et al, 2019). This study implemented a thorough cooperation with the projects reference group, consisting of an older woman living with incurable cancer living at home, a former informal caregiver, who previously cared for a home-dwelling older woman with incurable cancer, a general practitioner and two oncology nurses employed in the municipal healthcare services.…”
Section: Patient and Informal Caregiver Participation In Researchmentioning
confidence: 99%
“…While collecting data on the ICs' experiences, reflecting upon our pre-understanding and focusing on collecting detailed descriptions, afforded study transferability. 37 As part of the methodological approach, we used the framework PAIC-PAIR part 1 21 to strengthen study trustworthiness 38 regarding the credibility and internal validity of the study; 38 two ICs contributed in all phases of the research process, as members of the steering group and advisory board. Dependability 38 was sought through a transparent documentation of the research process.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…We acknowledge both patients and IC representatives as experts with unique competence, valuable in all phases of the research process. Inspired by the Framework of patient and IC participation in research (PAICPAIR part 1) 21 we established contact with patient organizations in the planning phase of this research process to create a sound collaboration with ICs as co-researchers. Two ICs were recruited as co-researchers.…”
Section: Methodsmentioning
confidence: 99%